Brenda is a sheep - Hood, Morag (Two Hoots, 2019)
Brenda says she is a sheep, but why does she look so different from her fluffy friends? All the sheep adore Brenda. With her sharp pointy teeth and cool grey fur, she's the snazziest sheep around. But Brenda is also very hungry, and doesn't much like the taste of grass - she soon begins plotting the most delicious feast of all. But will the sheep notice that Brenda isn't quite the same as them?
Keywords: erilaisuus